2001
DOI: 10.1002/aoc.241
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymeric precursors for the formation of nanocrystalline Ti‐C‐N/amorphous Si‐C‐N composites

Abstract: The synthesis of trimethylsilyl-substituted poly(titaniumcarbodiimide) as a novel precursor for titanium carbonitride based ceramic materials is described. The precursor and the subsequent processing steps (cross-linking and pyrolysis) are characterized by IR and Raman spectroscopy, thermal gravimetric analysis and simultaneous mass spectroscopy, electron microscopy and powder X-ray diffraction measurements. The novel polymer is formed by the reaction of TiCl 4 or Ti(NEt 2 ) 4 with bis(trimethylsilyl)carbodiim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 27 publications
1
52
0
4
Order By: Relevance
“…The relative small amount of carbon in this material (Fig. 1) indicates the high loss of carbon containing molecular fragments during pyrolysis (mainly HCN, CH 4 , CH 3 CN, and (CH 3 ) 3 SiOSi(CH 3 ) 3 ), which we reported previously [7], investigated by thermal gravimetric analysis and simultaneous mass spectrometry.…”
Section: Morphology and Nanochemistry Of The Materialssupporting
confidence: 54%
See 2 more Smart Citations
“…The relative small amount of carbon in this material (Fig. 1) indicates the high loss of carbon containing molecular fragments during pyrolysis (mainly HCN, CH 4 , CH 3 CN, and (CH 3 ) 3 SiOSi(CH 3 ) 3 ), which we reported previously [7], investigated by thermal gravimetric analysis and simultaneous mass spectrometry.…”
Section: Morphology and Nanochemistry Of The Materialssupporting
confidence: 54%
“…In a foregoing paper [7] we presented general reaction conditions for the synthesis and the characterisation of the Ti-C-N-precursor by infrared absorption and Raman spectroscopy, and of the ceramic material by X-ray powder diffraction. In this paper, we report on the synthesis of nanocrystalline titanium carbonitride materials at different pyrolysis temperatures via the polymer-to-ceramic transformation [8][9][10] of a newly developed titaniumcarbodiimide polymer [7] and their structural and nanochemical characterisation using high-resolution and analytical electron microscopy in combination with quantummechanical calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface modification of the aerogel for different silylation periods from 6 to 24 h is confirmed by the FTIR spectra of the aerogels as shown in figure 15. It was observed that with increasing silylation period, the intensity of -OH bond peaks at 1600 and 3400 cm −1 [35] decreased, and the peaks related to C-H at 2960 and 1450 cm −1 and those related to Si-C at 840 and 1260 cm −1 increased [36]. Thus, the dependence of surface modification on the silylation period was clearly observed.…”
Section: Effect Of Silylation Periodmentioning
confidence: 90%
“…Peaks attributed to Si-O-Si symmetric stretching vibrations and bending mode was observed around 1100 cm −1 and 800 cm −1 , respectively [27,28]. In the case of SiOC(-H) films, the intense band between 1020 cm −1 and 1250 cm −1 is related to Si-O-Si and Si-O-C asymmetric stretch modes [29].…”
Section: B Chemical Structure Of the Sioc(-h) Filmsmentioning
confidence: 95%